Building Relationships, Sustaining Communities: Decolonial Directions in Higher Ed Bluegrass Pedagogy - Stimeling, Travis; Enriquez, Sophia (Intersections, 2019)
Recent debates about bluegrass music’s place in higher education have highlighted anxieties about the historic role that institutions of higher education have played in cultural colonization, erosion, and destruction. Using examples from the bluegrass band at a large Appalachian public university, this essay considers how the “bluegrass jam” might facilitate meaningful conversations about identity in a region subjected to colonial-style extraction for nearly three centuries. At the same time, this article problematizes the nature of the university’s simultaneous support of regional culture and the propagation of resource extraction and environmental decay.